Great and Not So Great. Book Review: Sokolov, B.V. (2024). One Hundred Great Philologists (100 great). Moscow: Veche Publ. (In Russ.). - Alexander G. Kovalenko; Daria A. Mamaeva (RUDN Journal of Studies in Literature and Journalism)
-